UJI DAYA HAMBAT EKSTRAK DAUN BANDOTAN (Ageratum conyzoides L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Melsi Mengkido; Orryani Lambui; Wahyu Harso (Biology Department, Mathematics and natural science, Tadulako University, 2019)
Ageratum conyzoides L. is commonly known as weed species however leaf from this plant is used as traditional medicine for wound and skin infection. Furthermore it is important to test A. conyzoides L. leaves extract can inhibit the growth of Staphylococcus aureus bacteria which is causing infection disease. The content of this leaf which can inhibit bacterial growth is also obeserved. The study was conducted by growing S. aureus bacteria on nutrient agar (NA) and then a number of leave extract from A. conyzoides leaves (7.5, 15.0, 35 and 50%) were injected to NA by well diffusion method. Amoxicillin 0,6% and DMSO 1% were also injected as positve control and negative control respectively. Inhibition zone was measured based on diameter formed. The results showed that increasing leaves extract increased inhibition of S. aureus growth however 50% leave extract inhibited S. aureus growth less than Amoxicilin 0,6%.A. conyzoides leaf can inhibit S. aureus growth may be caused by terpenoid, fenol, saponin and alkaloid on its content.